2005
DOI: 10.2106/jbjs.d.02585
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Proteins<sbt aid="1014249">Development and Clinical Efficacy in the Treatment of Fractures and Bone Defects</sbt>

Abstract: The discovery of bone morphogenetic proteins marks a major step forward in the understanding of bone physiology and in the development of advanced methods in skeletal surgery. The cornerstones for successful growth-factor therapy in skeletal surgery remain biomechanical stability and biological vitality of the bone providing an adequate environment for new bone formation. Knowledge of the biological characteristics, mechanisms of action, and methods of delivery of growth factors will become essential for skele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
153
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(160 citation statements)
references
References 112 publications
2
153
0
2
Order By: Relevance
“…Of the BMPs, BMP-2, 6, and 9 have been shown to be the most potent agents in inducing osteoblast differentiation of mesenchymal stem cells. On the contrary, BMP-3 exhibits no osteogenic activity and antagonizes the osteogenic activity of BMP-2, 4, 6, 7, and 9 [16].…”
Section: Introductionmentioning
confidence: 97%
“…Of the BMPs, BMP-2, 6, and 9 have been shown to be the most potent agents in inducing osteoblast differentiation of mesenchymal stem cells. On the contrary, BMP-3 exhibits no osteogenic activity and antagonizes the osteogenic activity of BMP-2, 4, 6, 7, and 9 [16].…”
Section: Introductionmentioning
confidence: 97%
“…In 1988, Wozney et al [49] identified the genetic sequences of BMPs. Since then, over 20 different BMP-homologous molecules have been described, 15 of which were identified in humans [43]. BMPs belong to the transforming growth factor-b superfamily, a large family of growth and differentiation factors, which are involved in several stages of embryonic organogenesis and in various stages of intramembranous and endochondral ossification during fracture healing [19,36].…”
Section: Introductionmentioning
confidence: 99%
“…BMP quickly gained favor due to its unique ability to induce chemotaxis of progenitor cells and induce differentiation and proliferation of mesenchymal cells into cartilage and bone-forming cells. [1][2][3][4][5] The landmark discovery of BMP by Urist marked a major turning point in the understanding of bone physiology, and has dually influenced the clinical management of resistant and delayed unions in orthopedic surgery. The current management for the majority of pseudarthrosis cases includes mechanical stabilization with various forms of internal or external fixation in addition to some form of a biological stimulation.…”
Section: Introductionmentioning
confidence: 99%